The above series is arithmetic series. The formula for finding the sum of arithmetic series if given the the first tern, the last term and number of terms of terms is n( t1 + tn)/2, where t1 is the first term and tn is the last term.

n = 6

t1= -7

tn = -17

So it will be 6(-7 + -17)/2 = 6(-24)/2 = -144/2 = -72.

I am giving you an alternative approach in my next submission.

May 16th, 2015

You can also use the formula

S_{n} = n/2 * ( 2a_{1} + (n-1) d )

where Sn is the sum, n is the number of terms, a1 is the first term, and d is the common difference

n = 6

a1= 7

d = -9 - -7 = -2

Sn = 6/2( 2 x -7 +(6-1)-2)

Sn = 3(-14 + (5 x -2))

Sn = 3(-14 -10)

Sn = 3 x -24

Sn = -72

Hope this helps! You can ask any question if you are not satisfied.